Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Grab - Indri Ramadani; Rismawati Rismawati; Nasrudin Nasrudin; Parenta Ritonga; Suri Purnami (Universitas 45 Surabaya, 2024)
One technology that helps in the advancement of public transportation services is the internet. In Indonesia there are already applications that offer public transportation services that dominate in terms of transportation services such as Grab, Gojek and Uber. Some of these applications offer different services ranging from motorcycle taxis, car taxis, car rental, motorcycle rental, shopping to massage services. One of the online motorcycle taxi service applications in Indonesia that is currently being used is Grab Bike. Grab Bike is a motorcycle taxi transportation company that aims to connect Grab Bike drivers with customers. Grab Bike as a transportation service company is an important company at this time, so Grab Bike is slowly developing its market share in Indonesia. The increase in Grab Bike customer satisfaction every year is thought to be due to several factors, including price and service quality. The purpose of this study was to determine the effect of price and service quality on Grab customer satisfaction in Medan city. This research uses quantitative research methods with descriptive research types which include validity, reliability, classical assumption tests, hypothesis testing (t test, f test, and R2 determination coefficient analysis test). The data analysis technique used in this research is Multiple Regression analysis using the SPSS version 25 data processing program with 96 respondents. The data collection technique used was distributing questionnaires and literature studies. The results showed that price and service quality partially and simultaneously had a positive and significant effect on customer satisfaction. The results of the Multiple linear regression test show that the Price variable is a variable that has a greater and dominant influence on the customer satisfaction variable as evidenced by the value of 35.1% compared to the service quality variable which obtained a beta value of 26.3%. The research results from the coefficient of determination test (adjusted R Square) show that the price and service quality variables are able to explain 59.5% of the influence that occurs on the customer satisfaction variable while the remaining 40.5% is influenced by other variables not examined in this study.